最後一哩課程對四技護生學習成效之探究 The Implementation and Learning Effects of Last-Mile Curriculum among Nursing Students of a Four-Year Technology College - 劉杏元 Hsing-Yuan Liu; 張家臻 Chia-Chen Chang; 于桂蘭 Kuei-Lan Yu; 何英奇 Ying-Chyi Ho; 曾銀貞 Yin-Jen Tzeng; 吳曉明 Sheam-Ming Wu (Journal of Research in Education Sciences, 2010)
本研究旨在探討「最後一哩」課程介入，對四技護生專業能力、專業承諾及工作愉悅感之學習成效。採量化研究為主，以橫斷式調查研究設計，輔以質化研究取徑。以立意取樣方式，選取北部某技術學院四技護理系學生共114 人為研究對象，運用「護理專業能力量表」、「護理專業承諾量表」、「工作愉悅感量表」及反思日誌為研究工具，進行資料的蒐集。研究發現：最後一哩課程的介入對護生的專業能力、專業承諾及工作愉悅感均具成效。本研究結果可提供護理教育課程規劃之有效參酌。 The purpose of this study was to investigate the learning effects of the Last-Mile Curriculum on the professional competence, professional commitment, and sense of work excitement of college nursing students using both quantitative and qualitative methods. The purposive sampling consisted of 114 nursing students from a four-year technology college in Northern Taiwan. Three quantitative instruments were used, including self-administered questionnaires of the nursing professional competence scale, the nursing professional commitment scale, and the sense of work excitement scale for data collection before and after the whole Last-Mile clinical practice curriculum. Reflection journals were also used as qualitative supplements for this study. The results showed positive effects on the implementation of the Last-Mile Curriculum on the professional competence, professional commitment, and sense of work excitement of nursing students. Therefore, the results of this study provide useful references for future course planning of nursing education.